Absolute Lymphocyte Count Predicts Immune-Related Adverse Events in Patients With Non-Small-Cell Lung Cancer Treated With Nivolumab Monotherapy: A Multicenter Retrospective Study - Egami, Saeka; Kawazoe, Hitoshi; Hashimoto, Hironobu; Uozumi, Ryuji; Arami, Toko; Sakiyama, Naomi; Ohe, Yuichiro; Nakada, Hideo; Aomori, Tohru; Ikemura, Shinnosuke; Fukunaga, Koichi; Yamaguchi, Masakazu; et al. (Frontiers in Oncology, 2021)
Background: In patients with advanced non-small-cell lung cancer treated with nivolumab monotherapy, the association between peripheral blood count data (at baseline and at 2 weeks after treatment initiation) and the early onset of immune-related adverse events (irAEs) and treatment efficacy has not been clearly established. This study aimed to identify peripheral blood count data that may be predictive of the development of nivolumab-induced irAEs in a real-world clinical setting. Materials and Methods: This multicenter observational study retrospectively evaluated consecutive patients with advanced non-small-cell lung cancer undergoing nivolumab monotherapy in the second- or later-line setting between December 2015 and November 2018 at the National Cancer Center Hospital and Keio University Hospital. The primary endpoint was the association between peripheral blood count data and irAEs during the 6-week study period. Receiver operating characteristic curve and multivariate logistic regression analyses were performed. Results: Of the 171 patients evaluated, 73 (42.7%) had ≥1 irAE during the first 6 weeks following treatment initiation. The median time to irAEs from the initiation of nivolumab was 15 (interquartile range: 13–28) days. Receiver operating characteristic curve analyses revealed that the optimal cutoff values of the absolute lymphocyte count, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio at 2 weeks after treatment initiation for early irAE onset were 820, 4.3, and 2.2, respectively. In multivariate logistic regression analyses, absolute lymphocyte count >820 at 2 weeks after treatment initiation was significantly associated with an increased risk of early onset of any irAE. In contrast, no significant association was observed for the neutrophil-to-lymphocyte ratio (>4.3) or the lymphocyte-to-monocyte ratio (>2.2) at 2 weeks following treatment initiation. Conclusions: Absolute lymphocyte count >820 at 2 weeks following nivolumab initiation predicts early onset of irAEs during a 6-week study period. Routinely available absolute lymphocyte count measured after the initiation of nivolumab may be useful for identifying patients at risk of early onset of irAEs.